Lumpy Skin Disease Virus Infection: A Mini-review of Transmission, Diagnosis, and Control - Hasan, Mahamudul (PSM Microbiology, 2021)
Lumpy skin disease (LSD) belonging to a Capripoxvirus genus and is one form of viral infection affected by the lumpy skin disease virus (LSDV). In particular, the population of cattle and buffalo are vulnerable to the virus. The illness is typically characterized by the presence of a nodule in the eyelid, muzzle, limb, and udder. Presently, like an emerging disease, this pathogen is spreading to various areas, including Asia, Africa, and the Middle East. LSDV is responsible for reducing milk production, disruption to the hide and skin, abortion, mastitis, etc. Additament, in cattle and buffalo pathogens, its seriousness often causes death, suggesting the greater economic effect of this disease on the farmers and livestock industry. However, the key pillars for reducing the outbreak of this disease are adequate diagnosis, control, strict quarantine initiatives, and vaccination. There have been several studies to assess the prevalence of disease outbreaks, but few studies have been performed to present the current methods of diagnosis, control, and transmission. This mini-review is, therefore, aimed at providing the latest diagnostic and control measures for development. It will also address the propagation and economic significance of this disease to avoid further outbreaks.